The Effect Of Trust And Convenience On Customer Satisfaction With Purchasing Decisions As An Intervening Variable Purchase Decision As An Intervening Variable E-Commerce On Shopee In Medan City - Sucitra, Sucitra (Indonesian Journal of Economics and Finance, 2024)
The purpose of this research is to test and analyze the influence of Trust and Convenience on consumer satisfaction with purchasing decisions as an intervening variable for E-Commerce at Shopee in Medan City directly and indirectly. The approach used in this research is an associative approach. The population in this research is all E-Commerce consumers at Shopee in Medan City whose number is unknown. The sample in this study used the lameshow sampling technique, totaling 100 E-Commerce consumers at Shopee in Medan City, Medan. The data analysis technique used is path analysis using SEM-PLS. The results of this research show that Trust has a significant effect on Consumer Satisfaction through Purchasing Decisions as an intervening variable because it has a P Value of 0.010, so 0.010 < 0.05, thus it can be stated , and Convenience has a significant effect on Consumer Satisfaction through Purchasing Decisions as an intervening variable because it has a P Value of 0.006 so 0.006 < 0.05.